Pengaruh Likuiditas, Solvabilitas, Dan Profitabilitas Terhadap Perubahan Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Tahun 2012-2014 - Yuniarsi, Ika, Dra. Chuzaimah, M.M (2017)
This research aims to know the influence of liquidity, Solvency, and profitability to changes in Earnings at the manufacturing companies listed on the Indonesia stock exchange in 2012-2014. This research is quantitative research using secondary data. The population in this research is all the manufacturing companies listed on the Indonesia stock exchange (BEI) in 2012-2014. The sample in this research is the manufacturing companies listed on the Indonesia stock exchange (idx) of the period of 2012-2014. Technique of data analysis in this study by using multiple linear regression analysis. The results showed liquidity (Current Ratio) has no effect to changes in earnings at the manufacturing companies listed on the Indonesia stock exchange in 2012-2014 period. Evidenced by the value 0.05 > 0820 significance. Solvency (Debt to Equity Ratio) has no effect to changes in earnings at the manufacturing companies listed on the Indonesia stock exchange in 2012-2014 period. Evidenced by the significance of 0949 > 0.05. Profitability (Return On Asset) has no effect to changes in profit on manufacturing companies listed on the Indonesia stock exchange in 2012-2014 period. Evidenced by the value 0.05 > 0420 significance simultaneously liquidity, solvency, and profitability has no effect to changes in earnings at the manufacturing companies listed on the Indonesia stock exchange in 2012-2014 period. Evidenced by the Significance value of 0, 0.05 > 863. Key words: Solvabilita, Liquidity, profitability, changes in profit